Equal Opportunity in the Educational System and the Ethics of Responsibility - Philippe, De Villé (Les Cahiers de Recherche du Girsef, 2019)
To be "just", a society should treat every child fairly, i.e. with equal concern with regard to his potential education achievements. A person's educational achievements is indeed essential for enhancing her capacity for self-development: ideally, they all should have the same opportunities for achieving a level of formal education that would allow them to further study and compete for the jobs that they are fit for. This requires that the allocation of public educational resources among children should satisfy some principles of justice. Alongside objectives in terms of equality of "extended resources", recent theories of justice have emphasised the importance of taking into account personal responsibility in the design of equal opportunity policies. Allocation rules of educational expenditures should compensate for difference in non-controllable (by the child) determinants of school achievements, but also let freely determined effort levels to be adequately rewarded. Some allocation rules inspired by those requirements are discussed and the underlying reasoning for considering them are questioned along four different dimensions : 1. the child's effort and its determinants 2. the child's "school achievement production function": i.e. substitutability or complementarity between the determinants of school achievements, 3. the importance of externalities within the class room (peer effects) 4. the structure of the secondary school curricula. It is argued that all those dimensions are justifying the importance given to equal opportunity considerations but are also essential in identifying what should be the basic features of an equal opportunity strategy. In particular, they suggest that the focus on responsibility as one essential dimension in the design of such a strategy might be misplaced. But it also points out that an equal opportunity strategy consisting of compensating for inequality in endowments among children should also carefully incorporate various incentives mechanisms that will both enhance the effectiveness of the equality of opportunity strategy while contributing at the same time to the maximisation of the total human capital acquired by the children. Section 1 discusses what is the "equal opportunity" approach to schooling, its raison d'être. Section 2 reviews and critically discuss the basic "equal opportunity" model and its implications. Sections 3 and 4 present modifications and extensions of this framework and section 5 concludes with some policy recommendations.